Educational technologies for health education on stroke: an integrative review - Samia Jardelle Costa de Freitas Maniva; Zuila Maria de Figueiredo Carvalho; Regina Kelly Guimarães Gomes; Rhanna Emanuela Fontenele Lima de Carvalho; Lorena Barbosa Ximenes; Consuelo Helena Aires de Freitas
ABSTRACT Objective: to identify in the scientific literature the educational technologies used in the health education process related to stroke. Method: integrative review, whose eligibility criteria of the articles were: match the keywords "health education" and "stroke"; be a research paper; be in Portuguese, English and Spanish; be available electronically in the databases LILACS, PubMed/Medline, Scopus and CINAHL; year of publication between 2000 and 2016. Results: 24 publications were found. The analysis was carried out by means of analytical and interpretive readings. There were many educational technologies used in the health education process for stroke. Final considerations: the printed material for general public stood out, aiming to the recognition of alert signs of the disease and the emergency decision-making before suspicious cases of the disease.